Pengaruh Sikap Konsumen terhadap Marketing Mix Hospitality - Kusuma Chandra Kirana (Telaah Bisnis, 2016)
AbstractYogyakarta has been known as the city of tourism for the many culture and heritage in this region. The city of Heritage attached to it, has an impact on people’s behavior in the consumption of products or services. A demand for good tourism on the products service has encouraged the growth of industries that promote values. Hospitality, an industry engaged in social services, is growing rapidly in Yogyakarta. The industry deals with hospitality services and management of socio-religious events, such as weddings. Based on the data obtained, people of Yogyakarta are very sensitive to the appropriate product warranties. This study used descriptive statistics of Likert shari’i scale, a modified Likert scale. Data were analyzed using Fishbein formulation. The results of the above studies indicate that the overall consumers’ attitude towards hospitality marketing mix in Yogyakarta is positive with the value of Ao: + 5.1601. On the other hand, the score of partial assessments of hospitality marketing mix in Yogyakarta are as follows; product assessment Ao = +1.047025, price Ao =0.58305, location Ao = +0.980075, promotion Ao = +0.3479.